Productivity spillovers from R&D, exports and FDI in China's manufacturing sector - Wei, Y; Liu, X (Journal of International Business Studies, 2006)
This paper assesses productivity spillovers from R&D, exports and the very presence of foreign direct investment (FDI) in China's manufacturing sector, based on a panel of more than 10,000 indigenous and foreign-invested firms for 1998–2001. There are positive inter-industry productivity spillovers from R&D and exports, and positive intra- and inter-industry productivity spillovers from foreign presence to indigenous Chinese firms within regions. OECD-invested firms seem to play a much greater role in inter-industry spillovers than overseas Chinese firms from Hong Kong, Macao and Taiwan within regions. The findings have important managerial and policy implications.